MENINGKATKAN HASIL BELAJAR SISWA MELALUI METODE TANYA JAWAB PADA SISWA KELAS I SD NEGERI PANIKI - Isyah, Isyah (Bajang Institute, 2024)
This study aimed to explore the effectiveness of utilizing visual media to enhance children's reading abilities. The participants consisted of 11 early childhood learners aged 6-7, comprising 2 girls and 9 boys. Employing the Classroom Action Research (CAR) method, specifically the Question and Answer technique, the study conducted two cycles with two sessions in each cycle. The findings indicated a significant improvement in children's reading skills through the use of visual media. Hence, educators are recommended to employ visual aids creatively to enhance children's reading proficiency.